PENINGKATAN PRODUKSI DENGAN CARA MENDESAIN ULANG PROGRESSIVE CAVITY PUMP (PCP) PADA SUMUR “E” LAPANGAN “P” - Eko Prastio; Abdullah Rizky Agusman (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
Artificial lift method in an oil well is a production engineering that use the help of surface and downhole equipment in order to achieve optimum production when the well is not suited to use natural flow as the main lifting system. But in many cases, even after artificial lift method have using, the optimum production have not achieved yet, thus resulting a redesign of the existing artificial lift is needed. This problem exists on E well that is owned by PT XYZ 1 Field Jambi using Progressive Cavity Pump (PCP) as artificial lift. From the early calculation, it is found that the current production of 17,16 bfpd has not reached the targetted production that is 48,57 bfpd. This shows a need for the existing PCP to be redesigned. Before redesigning the artificial lift, the current value of Productivity Index (PI) is needed in order to make an Inflow Performance Relationship (IPR) curve that will shows whether the oil well still worth producing or not. According to the results of this research, the value of PI is 0,47 with the maximum production at 60,72 bfpd and optimum production 48,57 bfpd. Meanwhile, the current production is only 17,16 bfpd. After the redesigning completed using R & M Energy Systems calculation methods as the provider of the current PCP, it is found that the optimal for revolution per minute (RPM), horse power (HP), torque values and the drive head type are 101,5 RPM, 2,7 HP, 15 ft-lbs and there have to be a change in drive head type AA4. To get results optimal production.